Differential Scanning Calorimetric Study of Solidification Behavior of Monoacylglycerols to Investigate the Cold‐Flow Properties of Biodiesel. (25th July 2019) - Seniorita, Latifa; Minami, Eiji; Yazawa, Yoshiteru; Hayashi, Hitoshi; Saka, Shiro
Abstract: Monoacylglycerols (MAG) are impurities present in biodiesel as a result of incomplete reactions. MAG often solidify in biodiesel even at room temperature because of their high melting points. This worsens the cold‐flow properties such as the cloud point and pour point. We hypothesized that several types of MAG solidify simultaneously; therefore, we performed differential scanning calorimetry of binary mixtures of MAG to elucidate their interactions during solidification. Three thermodynamic formulas were then applied to the experimental results: (1) non‐solid‐solution, (2) solid‐solution, and (3) compound formation models. Binary mixtures of MAG showed complicated liquidus curves with multiple upward convex shapes, with which only the compound formation model fitted well. This model was applied to multicomponent mixtures that consisted of MAG and fatty acid methyl esters (FAME) as surrogate biodiesel fuels. We confirmed that the model still worked well. The results show that the compound formation model has good potential for predicting the cold‐flow properties of biodiesel.